Gestión de riesgos laborales y comportamiento de los trabajadores en la construcción de caminos vecinales. Loreto 2024 - Solsol Ruiz, Jose Remigio (2024)
It is a non-experimental study of the exploratory, descriptive, analytical, cross sectional type, with the purpose of evaluating the cognitive and behavioral abilities of the workers of Diamante Azul and San Juan de Ungurahual, in the construction of local roads in the district of Alto Nanay. The primary information was obtained by applying a structured interview to 100% of the construction workers with a Cronbach's alpha of 0.717, with acceptable reliability of the instrument. The data obtained do not show a normal distribution according to the Shapiro-Wilk test, which is why the non parametric Rho Spearman test was used in the correlation analysis, concluding: The ability of workers to interpret plans and technical specifications is adequate in most, but additional training is still required for those who are deficient in this area. Although the majority follow safety procedures, a considerable proportion do not do so consistently, indicating the need to reinforce workplace safety training and supervision. The majority of workers always use the appropriate PPE, a small proportion show inconsistency in their use, which highlights the importance of continually promoting the correct use of PPE. The Rho Spearman test shows that there is a significant correlation between occupational risk management with the knowledge and behavior of workers. This is why improving risk management can have a positive impact on the safety and effectiveness of workers.